Evaluation of CNS Depressant Activities of Ethanolic Extract of Ficus bengalensis (Moraceae) Leaves - Ashikur Rahman, Md (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Phytochemical analysis of the dried leaves of Ficus bengalensis (Moraceae) indicated the presence of flavonoids, alkaloids, triterpenoids, tannins, saponins and steroids. The pharmacological interest of these compounds, coupled with the use of this plant in traditional medicine prompted the authors to check for its possible CNS depressant activities in animal models. METHODS: In CNS depressant test; hole cross, open field, beam walking and thiopental sodium-induced sedative test was studied. RESULTS: In CNS-depressant tests; hole cross, open field, beam walking and thiopental sodium-induced sedative test in mice it significantly (p<0.005, p<0.001) decreased the locomotor activity in mice. CONCLUSION: The obtained results provide a support for the use of this plant in traditional medicine and its further investigation.